2001
DOI: 10.1002/dvdy.1205
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor receptor 2 (Fgfr2) plays an important role in eyelid and skin formation and patterning

Abstract: Initiating as protruding ridges above and below the optic vesicle, the eyelids of mice grow across the eye and temporarily fuse in fetal life. Mutations of a number of genes disrupt this developmental process and result in a birth defect, "open-eyelids at birth." Here we show that a critical event for eyelid induction occurs at embryonic day 11.5 (E11.5) when the single cell-layered ectoderm in the presumptive eyelid territory increases proliferation and undergoes morphologic transition to form cube-shaped epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 57 publications
7
56
1
Order By: Relevance
“…As described previously in mice chimeric for Fgfr2 (Li et al, 2001) or that carried homozygous deletion of the b isoform of Fgfr2 (De Moerlooze et al, 2000), eyes from Cre-positive, Fgfr2 loxP/loxP embryos showed defective eyelid formation and failure of eyelid closure. Because LeCre is expressed within and around the lens placode, the surface ectoderm cells that give rise to the eyelids also lack Fgfr2.…”
Section: Eye Development After Targeting Fgfr2 In the Lens And Ocularsupporting
confidence: 55%
See 1 more Smart Citation
“…As described previously in mice chimeric for Fgfr2 (Li et al, 2001) or that carried homozygous deletion of the b isoform of Fgfr2 (De Moerlooze et al, 2000), eyes from Cre-positive, Fgfr2 loxP/loxP embryos showed defective eyelid formation and failure of eyelid closure. Because LeCre is expressed within and around the lens placode, the surface ectoderm cells that give rise to the eyelids also lack Fgfr2.…”
Section: Eye Development After Targeting Fgfr2 In the Lens And Ocularsupporting
confidence: 55%
“…Previous studies of embryos with germ line deletion of Fgfr3 or Fgfr4, or chimeric mouse embryos with deletion of Fgfr1 (Zhao et al, manuscript submitted for publication) or Fgfr2 (Li et al, 2001) did not report lens phenotypes. In the present experiments, we targeted floxed Fgfr2 using a Cre transgene that can delete target genes in all lens cells beginning at embryonic day (E) 9.0 (Ashery- Padan et al, 2000).…”
Section: Introductionmentioning
confidence: 93%
“…1. They include the following: initiation (ectoderm morphogenesis and groove formation; E11.5), eyelid mesenchymal protrusion (E13.5), protruding epithelial ridge formation at the tip of the eyelid margin (E15) and subsequent extension of the upper and lower eyelid epithelium first (E15~16) and mesenchymal cells later (E16.5~17.5) (Li et al, 2001;Stepp, 1999). The upper and lower eyelid fusion occurs in the epithelium, and the mesenchymal cells are not fused for subsequent reopening.…”
Section: Resultsmentioning
confidence: 99%
“…In mice, eyelid formation begins on day 11.5 of gestation (E11.5), and from E14 to 16 the eyelids grow, flatten across the eye, progressively meet beginning at the inner and outer canthi and fuse tightly with each other (Harris and McLeod, 1982;Li et al, 2001). The eyelashes and the glands lying along the margins of the lids start to differentiate from this common epithelial lamina before the lids reopen at 14 days after birth (Findlater et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation